Autobiographical Memory and Episodic Specificity Across Different Affective States in Bipolar Disorder - Silva, Rafael de Assis da; Tancini, Marcelo Baggi; Lage, Renata; Nascimento, Rodrigo L.; Santana, Cristina M. T.; Landeira-Fernandez, J.; Nardi, Antonio Egidio; Cheniaux, Elie; Mograbi, Daniel C. (Frontiers in Psychiatry, 2021)
Autobiographical memory is essential to ground a sense of self-identity, contributing to social functioning and the development of future plans, and being an essential source for the psychiatric interview. Previous studies have suggested loss of autobiographical episodic specificity in unipolar depression, but relatively fewer investigations have been conducted in bipolar disorder (BD) patients, particularly across different mood states. Similarly, there is a scarcity of systematic investigations about mood-congruent and mood-dependent memory in relation to autobiographical memory in BD. Considering this, a total of 74 patients with BD (24 in euthymia, 26 in mania, and 24 in depression) responded with autobiographical memories to cue words belonging to 4 categories: mania, depression, BD and neutral. Episodic specificity was scored according to the Autobiographical Interview, with high intra- and inter-rater reliability. Results indicated that patients in mania generally re-experience more episodic details than those in depression. Depressed bipolar patients reported fewer details of perception and less time integration of memories than those in euthymia or mania. Words linked to depression and BD induced greater episodic re-experiencing than neutral words, just as words about BD provided greater episodic re-experiencing and more details of emotion / thoughts than words about mania. Words linked to depression provoked more time details about the recalled episodes than words on BD or neutral themes. No mood-congruent or mood-dependent effects were observed. Current findings may improve the ability of clinicians to conduct psychiatric interviews and the diagnosis of BD, with special attention to how memory details are generated across different mood states of the condition. Additionally, interventions to foster autobiographical recollection in BD may be developed, similar to what has already been done in the context of schizophrenia.